2016
DOI: 10.5455/msm.2016.28.66-70
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Therapy in the Treatment of Acute Corrosive Intoxication in Adults

Abstract: Introduction: Acute intoxications with corrosive substances can cause severe chemical injuries of the upper gastrointestinal tract, most often located in the mouth, pharynx, esophagus, stomach and duodenum. If a patient survives the acute phase of intoxication, regenerative response may result in esophageal and/or gastric stenosis, and increased risk of esophageal and gastric cancer. Such intoxication may be fatal due to perforation or tracheal necrosis. Enteral nutrition is a nutritional method when nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
1
10
0
2
Order By: Relevance
“…The Lugol's iodine solution used to detect the dysplastic areas of mucosa was sprayed onto the oesophageal surface from the gastro-oesophageal junction to the upper oesophageal sphincter using the dye-spraying catheter through the biopsy channel. This protocol is in agreement with the methods of Chibishew et al[12], who reported that the routine endoscopic biopsy of normal-appearing mucosa or biopsies guided by tissue staining with Lugol’s solution may increase the detection of dysplasia or mild oesophageal cancer. Narrow band imaging- magnifying endoscopy helps in visualization of oesophageal mucosa and surveillance of oesophageal precancerous lesions[21].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The Lugol's iodine solution used to detect the dysplastic areas of mucosa was sprayed onto the oesophageal surface from the gastro-oesophageal junction to the upper oesophageal sphincter using the dye-spraying catheter through the biopsy channel. This protocol is in agreement with the methods of Chibishew et al[12], who reported that the routine endoscopic biopsy of normal-appearing mucosa or biopsies guided by tissue staining with Lugol’s solution may increase the detection of dysplasia or mild oesophageal cancer. Narrow band imaging- magnifying endoscopy helps in visualization of oesophageal mucosa and surveillance of oesophageal precancerous lesions[21].…”
Section: Discussionsupporting
confidence: 87%
“…This result may be attributed to the fact that in liquid form, bases are tasteless and denser than water[13], while strong acids are bitter and are commonly expectorated[4]. Potash is potassium hydroxide, it used in oven cleaners, liquid agents, liquid drain cleaners, disk batteries household cleaners, dishwater detergents[12,13]. The median and range of patients’ weight and height by Z-score were -1.20 (-10.81-1.91) and -2.11 (-5.82-0.61), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La nutrición es uno de los aspectos terapéuticos más importante ya que contribuye en gran medida a la recuperación más rápida de las lesiones del tracto digestivo, la estabilización de los parámetros biológicos, inmunológicos y metabólicos, además de lograr disminuir la estancia en hospitalización. El soporte nutricional temprano es de gran importancia porque reduce las infecciones y el riesgo de desarrollar neumonía por aspiración y embolismo pulmonar 21,22 .…”
Section: Preservar El Estado Nutricional Del Paciente Es Otro Objetivo Del Tratamiento Y Para Ello Existen Diversas Alternativas a Considunclassified
“…Nutrition in the treatment of acute corrosive intoxications is one of the most important therapeutic processes that largely contribute to faster recovery, stabilization of biologic, immunologic and metabolic parameters and reduction of length of hospital stay. 8 Later patient had developed long, tight and nonnegotiable oesophageal stricture and was not able to take anything orally. In view of previous history of perforation, attempts of oesophageal dilatation were restricted.…”
Section: Discussionmentioning
confidence: 99%